The evolution and popularity of science play with specific reference to Marlowes Dr. Faustus, Brechts Galileo and Frayns Copenhagen - Ahmad Yas, Khalid; Ali Termizi, Arbaayah; Talif, Rosli; Hardev Kaur (Australian International Academic Centre, Australia, 2016)
This paper traces theatrically and statistically the evolution and popularity of science play from 1604, the publication of Marlowe’s Dr Faustus, to 2005 revealing reasons behind this popularity in particular within the last few decades. It also presents a brief classification of playwrights employed science in their works, and does analysis for major works that contributed much not only in the development and popularity of science drama, but also in the drastic change they have brought to this genre. Actually, from Marlowe to now, scientists and science have held a fascination for writers and audience on equal terms. In our genetic, atomic and tech-savvy climate, drama contains science of any kind will head directly to spotlight. The pivotal year of 1998, when Copenhagen was first premiered, has led to unprecedented wave of science plays. Science has become the vogue and science play has gone beyond using science as a sort of ornament to integrate it into the fabric of drama. Everything from Newton's Principia to Greene's books on String Theory has passed across the stage. Consequently, this wave of science plays has not only softened the earth for a permanent shift in our perception of science as a fundamental part of our culture and a legitimate and compelling subject for theatre, but also has brought the vision of ‘‘a third culture’’ into reality.